Dividend Policy's Role in Company Value: IDX Pharmaceutical Manufacturing (2013-2021) - Sari, Roro Yona Novita; Hanun, Nur Ravita (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the interplay between dividend policy, profitability, firm size, and firm value in the context of pharmaceutical manufacturing firms listed on the Indonesia Stock Exchange. Employing a purposive sampling technique, 54 companies were selected, and Smart Partial Least Square 3.0 program was utilized for statistical analysis. The findings reveal that while profitability exerts no significant influence on firm value, firm size positively impacts it. However, dividend policy does not moderate the relationship between profitability, firm size, and firm value. These results prompt further exploration into the nuanced dynamics of dividend policy and its implications for firm valuation strategies. Highlights : Profitability does not significantly affect firm value. Firm size positively influences firm value. Dividend policy does not moderate the relationship between profitability, firm size, and firm value. Keywords: Dividend policy, Profitability, Firm size, Firm value, Pharmaceutical manufacturing.